Accountability, Dependency, and EU Agencies: The Hotspot Approach in the Refugee Crisis. (2nd April 2018) - Horii, Satoko
ABSTRACT: EU agencies are central components of the "hotspot" approach the EU's newly developed border and asylum management mechanism in Greece and Italy amid the so-called refugee crisis in 2015. This article explores the constrains under which Frontex (border management), the European Asylum Support Office (asylum) and Europol (police cooperation), three core EU agencies, have implemented their tasks in the field, focusing on issues of accountability and dependency, in addition to the challenges they have embraced in their institutional designs. It argues that, whereas accountability arrangements are in progress, these EU agencies have been exposed to criticism related to their increasing and substantial roles. This article also reveals that these three EU agencies have remained largely dependent on the willingness of the EU Member States for sustainable task implementation. Based on the findings, this article critically assesses the EU's border and asylum management, referring to such aspects as the importance of civil society actors and the de facto role of the agencies.